Women's access to agricultural technologies in rice production and processing hubs: A comparative analysis of Ethiopia, Madagascar and Tanzania - Achandi, Esther L.; Mujawamariya, Gaudiose; Agboh-Noameshie, A.R.; Gebremariam, S.; Rahalivavololona, N.; Rodenburg, J. (Elsevier, 2018)
This study presents results from a farmer survey conducted with 560 rice farmers from 27 villages spread over five hubs (concentration areas of rice production and processing) in three different countries in Eastern Africa (Ethiopia, Tanzania and Madagascar). The main research objective was to assess women's access to rice technologies and constraints to adoption of technologies. Constraints were analyzed over five different categories: (1) institutional (2) access to agricultural inputs, (3) technology-contextual, (4) household and socio-cultural and (5) extension. Key providers of extension were public (government), Non-Governmental Organizations (NGOs) and international organizations. Our study identifies that the overarching constraints to technology adoption are institutional and cultural impediments and related to the mode of delivery of extension services. Furthermore, the Focus Group Discussions (FGD) with the women, revealed that empowerment of women in decision making at the household level can enhance women's access and engagement in better farming practices suggested under extension advisory services. This is specifically true where women are able to overcome the hurdles of acquisition of extension training and access to the improved technologies.